PENGEMBANGAN INSTRUMEN LITERASI SAINS DAN HASIL BELAJAR SISWA KELAS VI SD - N.M.S. Yantiningsih; I.W. Suastra; D.B. Sanjaya (PENDASI Jurnal Pendidikan Dasar Indonesia, 2022)
The present study aimed at developing scientific literacy instruments and science learning outcomes for sixth grade elementary school students. This study uses a research and development design with a 4-D model. The results of this study are, (1) In the define stage, conducting observations and interviews regarding the instruments that have been used at SD No. 3 Kerobokan Kaja. (2) At the design stage, the lattice of science literacy instruments and the lattice of science learning outcomes instruments are compiled, the grid is translated into a science literacy instrument in the form of an essay test consisting of 20 items and a science learning outcome instrument in the form of a multiple choice test. consisting of 40 questions. (3) At the develop stage, the content validity test of the scientific literacy instrument has been carried out and 18 items are declared valid with the result r11 = 0.81. The test of the validity of the contents of the science learning outcomes instrument obtained results as many as 37 items were declared valid with the results of r11 = 0.83. Then the instrument was tested on 50 students and the results showed that the scientific literacy instrument of 18 items was declared valid and the value of r1.1 was 0.797, namely the scientific literacy instrument had a high level of reliability. In the science learning outcomes instrument, 37 valid questions were obtained with an r1.1 value of 0.87, the level of difficulty obtained 8 difficult questions, 18 medium questions and 11 easy questions, the discriminatory power got 5 items in the poor category, 23 questions included in the sufficient category, and 9 items in the good category and the test of the effectiveness of the IPA learning outcomes instrument option showed that the 4 options did not function properly but almost all scores were above 5%, i.e. all distractors functioned well. Thus the development of scientific literacy instruments and science learning outcomes in this study is expected to be used as an example to measure and develop scientific literacy instruments and science learning outcomes in sixth grade elementary school students.